PENILAIAN DAYA TARIK OBJEK WISATA PANTAI PUTRI SERAYI KECAMATAN JAWAI SELATAN KABUPATEN SAMBAS - wati, Ervina; Said, Syafruddin; Nugroho R, Joko (JURNAL HUTAN LESTARI, 2013)
The research was conducted at Princess Beach tourist area in the district Serayi South Jawai Sambas district, for 2 (two) weeks from the date field effective December 20, 2012 to complete. This research aims to obtain data on the assessment of the potential attraction located in the District Serayi Princess Beach Tourism South Jawai Sambas district for the development of tourism in the area. The benefit of this study is to provide information about the potential that can be used as a tourist attraction in the area contained Serayi Princess Beach tourist area. Based on calculations of the entire acreage acquired attractiveness criteria 129.82 value obtained by summing each - each element are such natural beauty, unique natural resources, natural resources stand, the integrity of natural resources, natural resource sensitivity, choice recreational activities, air cleanliness and location, and the movement of visitors. Then compared with the value of the existing classification of elements based Weighted Value of the development area attraction beach serayi daughter has enough appeal areas (C) to be developed into a natural tourist attraction. Keywords: Beach, Potential, Fascination, Potential, Princess Serayi attractions